Primary mucinous cystadenocarcinoma of the breast with amplification of the HER2 gene confirmed by FISH – case report and review of the literature - Kucukzeybek, Betul Bolat; Yigit, Seyran; Sari, Ayşegul Akder; Rezanko, Turkan; Durak, Evren; Sadullahoglu, Canan (Polish Journal of Pathology, 2014)
Fifty five-years-old woman was presented to the general surgery upon the palpation of a mass in her left breast. In the excisional biopsy performed, partially cystic tumor of 2 × 1 cm with solid areas was macroscopically observed. After through microscopic examination, the patient was diagnosed as invasive mucinous cystadenocarcinoma and the tumor was found to be ER- and PR-negative and C-erbB2 (2+). In the fluorescent in situ hybridization, HER2/neu gene amplification was observed. Here, we present the clinical, cytological, morphological and immunohistochemical features of a very rare type of breast carcinoma, mucinous cystadenocarcinoma of the breast, with the review of the relevant literature.